Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/2167702618805742
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Memory in Adults Exposed to Childhood Violence: Remembering Genital Contact Nearly 20 Years Later

Abstract: There are some memories that time may never erase, but questions arise as to whether genital contact experienced in childhood is one of them. Recent research confirms the possibility of false memories of childhood sexual encounters, including as intensified in vulnerable individuals by debated clinical techniques (Bottoms, Shaver, & Goodman, 1996; Lilienfeld, 2015; Loftus, 1996). Yet clinical and memory theories should also address the matter of enduring memories for genital touch actually experienced in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 74 publications
1
40
0
Order By: Relevance
“…On this occasion, dissociative amnesia was widely covered in the media and French proponents were regularly invited to explain this mechanism. Nevertheless, there are other arguments for long statute of limitations that do not emphasize the trauma model of dissociative amnesia (e.g., Goldfarb, Goodman, Larson, Eisen, & Qin, 2019).…”
Section: Frequencies Of Discussion and Recovered Memories During Thementioning
confidence: 99%
“…On this occasion, dissociative amnesia was widely covered in the media and French proponents were regularly invited to explain this mechanism. Nevertheless, there are other arguments for long statute of limitations that do not emphasize the trauma model of dissociative amnesia (e.g., Goldfarb, Goodman, Larson, Eisen, & Qin, 2019).…”
Section: Frequencies Of Discussion and Recovered Memories During Thementioning
confidence: 99%
“…Nearly 20 years later, we contacted a subset of the child victims to examine their long‐term memory for the medical exam (Goldfarb, Goodman, Larson, Eisen, & Qin, in press). Lost memory of (or failure to disclose) being in the hospital was evident overall in 17% of the sample.…”
Section: Longitudinal Studies Of Child Maltreatment and Memorymentioning
confidence: 99%
“…Longitudinal studies have shown that young maltreated children can accurately retain salient memories of their maltreatment well into adulthood (Alexander et al, 2005; Goldfarb, Goodman, Larson, Eisen, & Qin, 2018; Goodman, Quas, Goldfarb, Gonzalves, & Gonzalez, 2019). Whilst acknowledging that the relationship between negative emotional events, such as maltreatment, and memory is complex, for many adults the greater the traumatic impact of the childhood event, the more accurate the memory of the event in adulthood (Goodman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%